An Analysis Students’ Errors In Pronunciation English Vowels at Third Semester of English Education Study Program - Ika Pratiwi; Ali Ajam; Sahrun Sudirman; Indry Widyasti Anwar (Peneliti.net, 2023)
The aim of this study is to find out the most pronounced vowel errors and what types of errors are made by the third-semester students of the English education study program at Khairun University. The research used a qualitative research method and the participants were twenty students at Khairun University. The results of the study can be concluded that the dominant error of vowel sounds made by students is the sound /i:/ reaching 62 (or 28.44%) and the data shows substitution is a type of pronunciation error made by students reaching (86.66%).